2011
DOI: 10.1097/prs.0b013e318213a141
|View full text |Cite
|
Sign up to set email alerts
|

Free Tissue Transfer with Distraction Osteogenesis Is Effective for Limb Salvage of the Infected Traumatized Lower Extremity

Abstract: Distraction osteogenesis in combination with free tissue transfer is a powerful technique that allows limb salvage, particularly when local and regional flaps are unavailable or inadequate. For infected nonunion of the tibia, it permits a staged approach that allows underlying osteomyelitis to declare itself and provides vascularized healthy soft-tissue coverage that facilitates repeated operations for the purpose of distraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…8 Our results support the good outcomes achieved by combined orthopaedic and plastic surgery procedures for post-traumatic bone and soft-tissue defects. 24,25 Ziran et al 26 and Salvana et al 27 have reported good outcomes from using a multidisciplinary team approach to treat chronic osteomyelitis. Ziran et al 26 compared their outcomes before and after the introduction of a dedicated multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…8 Our results support the good outcomes achieved by combined orthopaedic and plastic surgery procedures for post-traumatic bone and soft-tissue defects. 24,25 Ziran et al 26 and Salvana et al 27 have reported good outcomes from using a multidisciplinary team approach to treat chronic osteomyelitis. Ziran et al 26 compared their outcomes before and after the introduction of a dedicated multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,32,33 However, it remains indisputable that the main disadvantage of the Ilizarov technique is the tedious process with external fixation that may take months to perform. Intense pin-track pain appeared in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although Gosbell et al reported salvage of an ankle and foot with infected soft tissue and superficial malleolus using an experimental antifungal regimen of combination voriconazole and terbinafine therapy, bony involvement was limited in this patient 4. As reported recently by Chim et al, the use of distraction osteogenesis in combination with free tissue transfer has been used successfully for limb salvage of infected lower extremities following trauma 5…”
mentioning
confidence: 95%